(untitled) - Koestler, Arthur (London, 1964)
The Act of Creation begins where this view ceases to be true. Koestler affirms that all creatures have the capacity for creative activity, frequently suppressed by the automatic routines of thought and behavior that dominate their lives. The study of psychology has offered little in the way of an explanation of the creative process, and Koestler suggests that we are at our most creative when rational thought is suspended - for example in dreams and trance-like states. Then the mind is capable of receiving inspiration and insight.
Keywords: Creative ability,Khả năng sáng tạo